Understanding Privacy in Occupational Health Services - Heikkinen, Anne (Nursing ethics, 2006)
The aim of this study was to gain a deeper understanding of privacy in occupational health services. Data were collected through in-depth theme interviews with occupational health professionals (n=15), employees (n=15) and employers (n=14). Our findings indicate that privacy, in this context, is a complex and multilayered concept, and that companies as well as individual employees have their own core secrets. Co-operation between the three groups proved challenging: occupational health professionals have to consider carefully in which situations and how much they are entitled to release private information on individual employees for the benefit of the whole company. Privacy is thus not an absolute right of an individual, but involves the idea of sharing responsibility. The findings open up useful new perspectives on ethical questions of privacy and on the development of occupational health practices.